DEVELOPMENT OF A MEASUREMENT TOOL WITH SPECIAL REFERENCE TO AVARANA IN METABOLIC SYNDROME - S, *Priya.; M A, Shajahan; S, Remadevi. (International Journal of Ayurveda and Pharma Research, 2017)
In many instances the researcher cannot find an adequate or appropriate existing tool to measure an important construct- the theoretical variable that is supposed to measure. In these situations it will become necessary to develop a new instrument for measuring the particular construct. Failure to carefully develop a measurement instrument can result in invalid data. The steps involved in the development of such tools are complex and unknown to many. Hence, the systematic development of a reliable and valid instrument for measuring subjective states is outlined here to assist researchers in devising usable instruments.According to Ayurveda, the diseases are caused by derangement of Tridoshas- the dynamic force (Vatha), the transformation factor (Pitha) and the anabolic factor (Kapha). Avarana is the disturbances in the movement of Vathadosha by other factors in the body. In the present social scenario, majority of diseases of Vatha are the result of Avarana. Metabolic syndrome is one such lifestyle disease comprised of obesity, hyperglycemia, hypertension, hyper triglyceridemia and low HDL level. Majority of the symptoms of Avarana can be identified in patients presenting with Metabolic syndrome. This article outlines the methodology involved in the development and validation of a measurement tool, taking into consideration of Avarana in Metabolic Syndrome.